Living histories queer views and old masters - Ng, Aimee; Truax, Stephen 1985-; Brown, Jessica Bell; Tovey, Russell (The Frick Collection, 2023)
Living Histories: Queer Views and Old Masters is an exciting volume featuring the work of four New York-based artists, each presenting a single new work in conversation with celebrated paintings in The Frick Collection. The works place particular emphasis on issues of gender and queer identity typically excluded from narratives of early modern European art. The idea of commissioning four works to display at Frick Madison emerged when four masterpieces from the collection by Vermeer, Holbein and Rembrandt. were loaned to exhibitions. Works by Jenna Gribbon, Doron Langberg, Toyin Ojih Odutola and Salman Toor were commissioned to replace them alongside other works by these artists. This book is the result of the four New York artists’ responses to the Frick’s collection, and the conversations their work engendered
Ermittelt: Related exhibition:"Living Histories: Queer Views and Old Masters", September 30, 2021 to September 11, 2022, The Frick Collection
Keywords: Odutola, Toyin -- 1985-; Toor, Salman -- 1983-; Langberg, Doron -- 1985-; Gribbon, Jenna -- 1978-; Frick Collection; Geschichte 2018-2022; Geschichte 1500-1700; Sexualität; Sammlung; Rezeption; Malerei; LGBT; Kunst; Portrait painting / Exhibitions; Sexual minorities in art / Exhibitions; Art and society / Exhibitions; Gender minorities; Ausstellungskatalog -- Frick Collection -- 30.09.2021-11.09.2022 -- New York, NY